Evidence-based case report: Coinfection of COVID-19 in children and administration of antibiotics - Fifi Sofiah; Marselya Ulfa; Azwar Aruf; Raden Muhammad Indra (RSUP Dr Moh Hoesin Palembang, 2020)
A B S T R A C TBackground. COVID-19 in childrenalthoughmostly mild,but can also cause seriousillness and even death. Coinfection, especially bacterialcan increase the severity of thedisease. There is yet sufficient evidence about the role of antibiotics in childhoodCOVID-19 with coinfection.Objective. To review the available evidence on thecoinfection in childhood COVID-19 and the role of antibiotic administration.Method.Online literature search using Pubmed database, google scholar dan Cohcranelibrary Results.No study was found that directly evaluate the efficacy of antibiotic inchildhood COVID-19 with coinfection. Three meta-analyses found rates of coinfectionof 5.6%-14% and one case series identified a very high rate (94.2%). Most frequentpathogens included Mycoplasma pneumonia, Streptococcus pneumonia,andinfluenza/parainfluenza viruses. Two RCTsandone case series on antibioticadministration, but all three studies did not address coinfection status.All threestudies evaluated the combination of azithromycin and hydroxychloroquine. Nochanges in illness severity or mortality attributed to the medications, one studyindicated more rapid viral load clearance associated with azithromycin. ConclusionThere is a lack of evidence on the role of antibiotics in the management of childhoodCOVID-19with coinfection. Azithromycin can be considered in some cases.